1999
DOI: 10.1074/jbc.274.26.18709
|View full text |Cite
|
Sign up to set email alerts
|

p73 and p63 Are Homotetramers Capable of Weak Heterotypic Interactions with Each Other but Not with p53

Abstract: Mutations in the p53 tumor suppressor gene are the most frequent genetic alterations found in human cancers. Recent identification of two human homologues of p53 has raised the prospect of functional interactions between family members via a conserved oligomerization domain. Here we report in vitro and in vivo analysis of homo-and hetero-oligomerization of p53 and its homologues, p63 and p73. The oligomerization domains of p63 and p73 can independently fold into stable homotetramers, as previously observed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
132
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(139 citation statements)
references
References 22 publications
6
132
0
Order By: Relevance
“…This suggested that at least some p73α forms a complex with p73β. Moreover, it was also reported that the purified recombinant polypeptide of the putative p73 OD (amino acids 345-383) associated with itself, although it did not interact with the p53 OD [19]. As the p73 OD used in that study is present in all p73 variants, it is likely that p73 variants can interact with each other.…”
Section: Introductionmentioning
confidence: 74%
“…This suggested that at least some p73α forms a complex with p73β. Moreover, it was also reported that the purified recombinant polypeptide of the putative p73 OD (amino acids 345-383) associated with itself, although it did not interact with the p53 OD [19]. As the p73 OD used in that study is present in all p73 variants, it is likely that p73 variants can interact with each other.…”
Section: Introductionmentioning
confidence: 74%
“…The first is the interplay between p53 and p63/p73: although there is little evidence of heterotetrameric formation of p53-p63 dimers (Davison et al, 1999), several reports have indicated that p63/p73 have an increased affinity for p53 missense mutants (Di Como et al, 1999;Strano et al, 2000;Gaiddon et al, 2001). Specifically, p63 was reported to associate with the p53 mutants of HaCaT cells (Gaiddon et al, 2001).…”
Section: Activation Of Klf4 By Mutant P53mentioning
confidence: 99%
“…For example, p63/p73 may bind to REs not efficiently bound by p53 and recruit the latter via protein-protein interactions. However, oligomerization studies discourage this possibility, as p63 and p73 seem capable of heterotypic interactions with each other but not with p53 (Davison et al, 1999). Alternatively, a 'priming' model could be envisioned, in which p63/p73 could bind to a given chromatin-embedded RE not accessible to p53, and then modify said RE in such a way that it would now become 'visible' to p53.…”
Section: The P53 Family Membersmentioning
confidence: 99%